(untitled) (Heritage, 2023)
The United Kingdom is the colonial power that has best positioned its position and relationship with former colonies of any colonial power in history. First, the British Commonwealth of Nations was created as a grouping that connects the metropolis with a huge number of countries. In addition, the King of the United Kingdom is the head of state in fifteen independent countries that were once colonies. The status of dominion was also introduced, which does not encroach on the country’s sovereignty and membership in the OUN, but in all important moments, especially in war conflicts, this state militarily supports the United Kingdom. Among them are some of the largest countries in the world, Canada and Australia, as well as New Zealand, which is a large country by European standards. Capital flows, which are concentrated in London for a significant part, are particularly significant. Some of the world’s biggest financial powerhouses live in London. The United Kingdom’s exit from the EU gives it a position to more freely influence events in Europe and the world, and even in the EU itself. The future will show how far this country will play an extremely important role in world relations.